Developing a priority global research agenda for antimicrobial resistance in the human health sector: protocol for a scoping review - Alessandro Cassini; Raph L Hamers; Koe Stella Asadinia; Silvia Bertagnolio (BMJ Open)
Introduction To accelerate the response to the public health threat by antimicrobial resistance (AMR), the WHO is developing a Global Research Agenda for AMR in the human health sector that aims to provide a global and transparent assessment of priority knowledge gaps related to critical bacteria—including Mycobacterium tuberculosis—and fungi that inform control and response strategies to tackle AMR by 2030. A literature scoping review represents the first phase in a stepwise process, and we hereby outline the protocol to review current knowledge gaps and research questions on AMR in the human health sector.Methods and analysis This literature scoping review will follow the Arksey and O’Malley (2005) methodology and will include: (1) a hand search to identify relevant WHO guidelines and documents suggested by the WHO Steering Group for the AMR Global Research Agenda; (2) a grey literature search through a stakeholder mapping process and google searches of organisational websites; (3) a systematic search of relevant systematic reviews through bibliographic databases (PubMed, Embase and Web of Science); (4) screening of the reference lists of included studies. We will include relevant publications from the last 10 years (January 2012 to December 2021). Two researchers separately will review the yielded citations to determine eligibility based on predefined criteria. Relevant research questions with attributes will be extracted using a tool developed through an iterative process by the research team. Each identified research question will be classified and aggregated according to a conceptual framework (ie, ‘knowledge matrix’), composed of three themes (ie, Prevention, Diagnosis and Care & Treatment) and four cross-cutting domains (ie, Descriptive, Discovery, Development, Delivery). We will present numerical and thematic summaries of the knowledge matrix. A qualitative content analysis is out of the scope of this protocol.Ethics and dissemination The scoping review process will only involve identification, selection and analysis of documents available for use in the public domain, and will not include any personal information on individuals, therefore ethical approval is not required. The findings will be disseminated through a peer-reviewed publication and stakeholder meetings.